Position Depended Sybil Attack Detection using Efficient KNN technique with Clustering - Bedi, Rajeev; Singh, Baljinder; Devi, Meenakshi (International Journal of Computer Sciences and Engineering, 2019)
In today's world the wireless sensor network has great significant in application like defense surveillance, patient health monitoring, traffic control etc. As WSN utilize radio frequencies so there is threat of interference in network. These threats also include distributed denial of service in which the messages that are sent over the network may be attacked by unauthorized user. It would harm the confidentiality of the network user and the services of network. There are various algorithm that are utilized to detect Sybil attack in WSN but these schemes only stress on prevention of attack after it is occurred. This would leads to the loss of data and more consumption of limited network resources. So in this work we introduce a new algorithm that is based on clustering based KNN along with Euclidean distance. It would detect earlier the Sybil attack in WSN and prevent the data loss. The parameters like throughput, energy consumption etc are utilized to analyze the performance of this technique.